2015
DOI: 10.1021/am508154n
|View full text |Cite
|
Sign up to set email alerts
|

Seeding Atomic Layer Deposition of Alumina on Graphene with Yttria

Abstract: Integrating graphene into nanoelectronic device structure requires interfacing graphene with high-κ dielectric materials. However, the dewetting and thermal instability of dielectric layers on top of graphene makes fabricating a pinhole-free, uniform, and conformal graphene/dielectric interface challenging. Here, we demonstrate that an ultrathin layer of high-κ dielectric material Y2O3 acts as an effective seeding layer for atomic layer deposition of Al2O3 on graphene. Whereas identical Al2O3 depositions lead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Figure 1d schematically shows possible factors in the gate stack, such as interfacial trap, fixed charge, and dipole, that can strongly affect the charge transport in the channel and electrical performances of the transistor. Since a thin layer of yttrium metal has been confirmed to be an effective SL to improve the electrical performance of 2D‐TMDs, [ 21,24–26 ] it is also used as an SL in our FETs. As shown in the last graph in Figure , the yttrium SL indeed helps to increase V th in the MoS 2 TG‐FET, but the FET is still in depletion mode ( V th < 0 V).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1d schematically shows possible factors in the gate stack, such as interfacial trap, fixed charge, and dipole, that can strongly affect the charge transport in the channel and electrical performances of the transistor. Since a thin layer of yttrium metal has been confirmed to be an effective SL to improve the electrical performance of 2D‐TMDs, [ 21,24–26 ] it is also used as an SL in our FETs. As shown in the last graph in Figure , the yttrium SL indeed helps to increase V th in the MoS 2 TG‐FET, but the FET is still in depletion mode ( V th < 0 V).…”
Section: Introductionmentioning
confidence: 99%
“…The lower dangling bond density on the TMD surface causes the direct atomic layer deposition (ALD) of high-κ dielectrics to form islands instead of a continuous film [25]. The deposition of various dielectrics on 2D materials such as graphene, black phosphorus, MoS 2 , and WSe 2 has been extensively studied [25,26,27,28,29,30,31]; however, a detailed interface investigation of a high-κ dielectric on ReS 2 and ReSe 2 remains of interest. Although a high-κ dielectric has been used for ReS 2 based devices [15,16,19], the ReS 2 interface chemistry with Al 2 O 3 has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…This works well because physical vapor deposition does not rely on a surface dangle bond to the same extent as a chemical vapor process such as ALD. Examples of seed layers on 2D materials have been SiO x , 62 Yttria, 63 aluminum, [64][65][66] and titianium. 67 It was later shown that such a process is not scalable to ultra-thin dielectrics on CVD graphene since process residues lead to clustering of the metal seed layer.…”
Section: Functionalizationmentioning
confidence: 99%